(untitled) - Sternberg, Robert J. (Fort Worth, Texas, 1994)
Robert J. Sternberg, noted researcher on intelligence, brings his innovative approach to bear on introductory psychology by presenting the field as constantly in process. Juxtaposing the evolution of ideas and the evolution of organisms in search of adaptation to their environments, with his triarchic theory of human abilities, the second edition of Sternberg's text represents a new and viable approach to teaching introductory psychology.
Keywords: Psychology,Tâm lý học